SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN BALITA SEHAT SE-KECAMATAN SEI LEPAN MENGGUNAKAN METODE MULTI ATRIBUTTE UTILITY THEORY (MAUT) (STUDI KASUS: PUSKESMAS DESA LAMA) - Septia Fajarika (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
All hopes parents want a healthy toddler, but not all parents, especially mothers, understand about toddler health, how to care for toddlers, nutritional intake or nutritional quantities for toddlers, not all parents, especially mothers, understand that, so this causes toddlers to not get good health and an adequate dose of nutrition from mothers.To overcome the above problems, the Old Village Health Center made a selection program for healthy toddlers from Sei Lepan sub-district in order to help mothers understand more about toddler health, about the nutrition intake of toddlers and also so that the Old Village Health Center knows how many healthy toddlers there are in the District Sei Lepan, but the selection is still manual which requires a very long time.In order to avoid the above problems, it is necessary to build an application for a Healthy Toddler Selection Decision Support System in Sei Lepan District by using the Multi Attribute Utility Theory (MAUT) method, so that it can help the Old Village Health Center in the assessment process to make it more accurate and the decisions made are satisfactory.Keywords: Decision Support System, Healthy Toddler Selection, MAUT Method.